Analysis of the SUV Involved Pedestrian Crashes in Pennsylvania - Aaiad, Youssra (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This thesis addresses the pivotal challenge of predicting the SUV involved pedestrian crash severity and proposes improvements to existing methodologies, underscoring the substantial threat posed by such incidents. Utilizing a comprehensive dataset spanning five years from the state of Pennsylvania, USA, the study acknowledges and addresses the challenge of class imbalance through the application of the Synthetic Minority Oversampling Technique (SMOTE) for data augmentation. Methodologically, diverse artificial neural network (ANN) architectures are explored, with meticulous evaluation through K-fold cross-validation to ensure the robustness of the model. Descriptive statistics and correlation analyses are employed to investigate crash characteristics and inter-variable relationships. The outcomes underscore the efficacy of SMOTE in improving predictive accuracy. Beyond its primary predictive contributions, this research offers nuanced insights into factors impacting model efficacy. By addressing prevailing limitations and introducing an innovative approach to handling class imbalances, our research informs the development of interventions to enhance road safety. The findings carry crucial implications for policy and practice, with the ultimate goal of reducing pedestrian accidents and mitigating their severity.

ÖZ: Bu tez, SUV kaynaklı yaya kazası ciddiyetini tahmin etme konusundaki temel zorluğu ele almakta ve bu tür olayların oluşturduğu önemli tehdidin altını çizerek mevcut metodolojilerde iyileştirmeler önermektedir. USA’nin Pennsylvania eyaletinden beş yılı kapsayan kapsamlı bir veri setini kullanan çalışma, veri artırma için Sentetik Azınlık Aşırı Örnekleme Tekniğinin (SMOTE) uygulanması yoluyla sınıf dengesizliği sorununu kabul ediyor ve ele alıyor. Metodolojik olarak, modelin sağlamlığını sağlamak için K-fold çapraz doğrulaması yoluyla titiz bir değerlendirme yapılarak çeşitli yapay sinir ağı (YSA) mimarileri araştırılmaktadır. Tanımlayıcı istatistikler ve korelasyon analizleri, çarpışma özelliklerini ve değişkenler arası ilişkileri araştırmak için kullanılır. Sonuçlar, SMOTE'un tahmin doğruluğunu artırmadaki etkinliğini vurgulamaktadır. Bu araştırma, birincil öngörü katkılarının ötesinde, model etkinliğini etkileyen faktörlere ilişkin incelikli bilgiler sunmaktadır. Araştırmamız, mevcut kısıtlamaları ele alarak ve sınıf dengesizliğini ortadan kaldırmak için yenilikçi bir yaklaşım sunarak, karayolu güvenliğini artırmaya yönelik müdahalelerin geliştirilmesine bilgi sağlamaktadır. Bulgular, yaya kazalarının azaltılması ve ciddiyetinin hafifletilmesi nihai hedefiyle politika ve uygulama açısından önemli çıkarımlar taşıyor.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2024. Supervisor: Assoc. Prof. Dr. Mehmet Metin Kunt.
Keywords: Thesis Tez; Civil Engineering Department; Traffic Engineering--Road Safety; Pedestrian crash severity; road safety; artificial neural networks; SMOTE